2006
DOI: 10.1002/da.20130
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind comparison of olanzapine/fluoxetine combination, olanzapine, fluoxetine, and venlafaxine in treatment-resistant depression

Abstract: Based on preliminary evidence of its usefulness in treatment-resistant depression (TRD), an olanzapine/fluoxetine combination (OFC) was examined in comparison with olanzapine, fluoxetine, and venlafaxine in a TRD population. In this 12-week double-blind study, 483 subjects with unipolar, nonpsychotic TRD, with historic failure on a selective serotonin reuptake inhibitor (SSRI) and prospective failure on open-label venlafaxine, were randomized to an OFC or to an olanzapine, fluoxetine, or venlafaxine monotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
212
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(219 citation statements)
references
References 26 publications
3
212
1
3
Order By: Relevance
“…The fact that 21% of the placebo group dropped from the study (vs. 12.9% of the risperidone group) may be due to inadequate response to medication. Rapid response to an adjunctive atypical followed by convergence with a control group was found in the recent study by Berman et al (2007) and the combination studies also reported a quick response followed by a leveling off after a few weeks (Shelton et al, 2005;Corya et al, 2006).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The fact that 21% of the placebo group dropped from the study (vs. 12.9% of the risperidone group) may be due to inadequate response to medication. Rapid response to an adjunctive atypical followed by convergence with a control group was found in the recent study by Berman et al (2007) and the combination studies also reported a quick response followed by a leveling off after a few weeks (Shelton et al, 2005;Corya et al, 2006).…”
Section: Discussionmentioning
confidence: 68%
“…Finally, the small to moderate treatment effect may indicate that the study was underpowered. That other studies testing atypical antipsychotics as augmenting agents (Berman et al, 2007;Ostroff and Nelson, 1999;Shelton et al, 2001) and those with larger samples (Corya et al, 2006;Shelton, 2006) report a similar pattern (i.e., rapid response followed by convergence of treatment groups), suggests otherwise. In fact, a compelling reason to initiate an atypical antipsychotic augmenting agent sooner rather than later may be because several studies, including this one, have reported a significant response as early as 1 week into treatment (Barbee et al, 2004;Bouhours et al, 2004;Ostroff and Nelson, 1999;Shelton et al, 2001).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thase et al [18] includes two trials (study 1 and study 2). Response was defined as an improvement of C50% from baseline to endpoint on the HAM-D or the MADRS, and remission was defined as a MADRS total score of B10 and C50% reduction in MADRS total score in the trials except trials by Shelton et al [15] and Corya et al [17] (two subsequent MADRS total score B8), McIntyre and Gendron [22] and Mahmoud et al [24] (HAM-D-17 score B7), Bauer et al [20], El-Khalili et al [21] and Keitner et al [26] (MADRS total score B8), trial by Reeves et al [25] aripiprazole than receiving placebo (0.6 %) had a weight gain of 7 % or more [13]. The difference in weight gain with SGA adjunctive therapy was small, and no other adverse event related to metabolic function, such as changes in mean waist circumference, total cholesterol, high or low-density lipoprotein cholesterol, triglycerides, fasting plasma glucose, or haemoglobin A1C, was associated with aripiprazole augmentation in short-term trials.…”
Section: Aripiprazolementioning
confidence: 99%